Percutaneous extracapsular repair as a cost-effective alternative for treating cranial cruciate ligament deficiency in dogs - Griffon, Dominique J.; Mostafa, Ayman; Griffon, Etienne; Schaeffer, David J. (Frontiers in Veterinary Science, 2025)
ObjectiveTo evaluate the duration of surgery, cost, and outcomes associated with percutaneous placement of a lateral fabellotibial suture (pLFS) in dogs with unilateral cranial cruciate ligament deficiency (CCLD) treated in a low-cost clinical setting.Study designBlock randomized prospective clinical trial on 24 dogs.MethodsDogs underwent an exploratory arthrotomy and extracapsular repair (ECR) or pLFS. Intraoperative findings, cost, and duration of surgery were recorded. Each dog was evaluated preoperatively and 2, 6, and 12 weeks after surgery with a standardized owners’ questionnaire, clinical examination, radiography, thermal imaging, and pressure gait analysis. Outcomes were evaluated longitudinally within dogs and between groups.ResultsThe pLFS technique was faster (about 20 min) and more cost-effective (by about 100$) than the ECR repair (p = 0.01 and 0.03). The only major complication consisted of a surgical infection requiring revision surgery after pLFS. Limbs had less reduction in thigh diameter 2 weeks after pLFS (−1.2 ± 0.05%) compared to those treated with ECR (−5.5 ± 0.04%, p = 0.03). The pressure placed on the operated limb averaged 78% of that of the contralateral limb 2 weeks after pLFS compared to 43% after ECR (p = 0.04). Similar results were obtained when comparing the ratio of activated sensors and relative stance time. No differences in owner assessment, radiographic progression of osteoarthritis, lameness scores, girth diameter, and gait analysis at the walk and trot were detected between groups.ConclusionThe pLFS was faster, more cost-effective, and improved limb function at 2 weeks compared to the ECR. These results justify the consideration of the pLFS as a low-cost alternative to ECR.